THE EFFECT OF REPRODUCTIVE HEALTH EDUCATION ON ADOLESCENT GIRLS AS A MEASURE TO PREVENT ADOLESCENT SEXUAL BEHAVIOR - Farihah Indriani; Fibrinika Tuta setiani; kurniawan, anang; Sinta Anggariyanti (JIM - Journal International Multidisciplinary, 2025)
Abstract Reproductive health is a state of complete physical, mental, and social well- being, not merely the absence of disease or infirmity, but also encompasses all aspects related to the reproductive system, its functions, and processes. Adolescence is a period in which an individual develops from the first time they show signs of secondary sexual characteristics until they reach sexual maturity. The research was conducted at SMK X Banyumas. This type of research used a quasi-experimental method with a one-group pretest-posttest design. The population in this study consisted of 72 adolescent girls. The sampling technique used in this study was random sampling. Based on the results of the bivariate analysis using a paired T-test with a sample size of 35 respondents (N=35), the data shows that T-Calculated (23.854) > T-table (0.462) and the p-Value (0.000) < alpha value (0.05), which means that based on the hypothesis that Ha is accepted and Ho is rejected, it can be concluded that there is a difference in the sexual behavior of respondents before and after being given health education about the reproductive system at SMK X Banyumas.